Effects of ATF cladding properties on PWR responses to an SBO accident: A sensitivity analysis. (January 2022) - Alraisi, Ali; Yi, Yongsun; Lee, Suwon; Alameri, Saeed A.; Qasem, Maryam; Paik, Chan-Young; Jang, Changheui
Highlights: A station blackout in a PWR nuclear power plant was simulated using MAAP. The plant responses with ATF cladding materials during an SBO were evaluated. Sensitivity analyses were performed on hypothetical cladding materials. High enthalpy cladding materials can retard the hot leg rupture in PWR plants. Abstract: To investigate the effects of ATF cladding properties on the plant responses to severe accidents, short-term station blackout simulations and sensitivity analyses on hypothetical cladding materials were performed using MAAP code. For sensitivity analyses, 7 hypothetical cladding materials were used. Hypo-0 was the reference cladding whose properties are anticipated to show the poorest fuel performance during an STSBO. The input property values for Hypo-1 through Hypo-6 were selected by changing each variable independently while keeping the others at their reference values. The onset times for core uncovery and cladding oxidation were similar for all the simulation cases, implying that single property cannot affect the event times. A main conclusion is that a large enthalpy of cladding can delay the increase in temperatures of fuel and cladding by playing a role as a heat sink after the core uncovery occurs, resulting in the delayed hot leg rupture.